Telemedicine for Rural Healthcare Access: Evaluating Effectiveness in Reducing Health Disparities - Aria Pranatha; Jamil Khan; Razia Khan; Agus Darmawan (Journal of World Future Medicine, Health and Nursing, 2025)
Rural populations face persistent barriers to healthcare access due to geographical isolation, workforce shortages, and limited infrastructure. Telemedicine has emerged as a promising strategy to bridge these gaps by enabling remote consultations, diagnosis, and follow up care. Despite its increasing adoption, the effectiveness of telemedicine in reducing health disparities between rural and urban communities remains insufficiently evaluated. This study aims to assess the impact of telemedicine interventions on healthcare accessibility, patient outcomes, and equity in rural settings. A mixed-method approach was employed, combining quantitative analysis of service utilization data from 10 rural hospitals with qualitative interviews involving 85 healthcare professionals and patients. The findings demonstrate a 35% increase in patient access to primary and specialist care, alongside a significant reduction in appointment wait times and emergency referrals. Qualitative insights indicate enhanced patient satisfaction and continuity of care, though infrastructural and digital literacy barriers persist. The study concludes that telemedicine substantially improves healthcare equity in rural areas but requires sustained investment in technology, training, and policy integration to ensure long term scalability and inclusivity. The results contribute to evidence based policy frameworks for digital health expansion in underserved regions.